Investigating the Impact of Order Flow Imbalance and Information Asymmetry on Treasury Bill Price Changes - Ali Namaki; Aysa Kazemi bavil (تحقیقات مالی)
ObjectiveThe information-based model is one of the prevalent frameworks in the market microstructure literature, examining trader behavior in the presence of information asymmetry and its subsequent impact on price formation. Information asymmetry significantly contributes to market inefficiency, manifesting in traders' transactions and orders. Informed traders, possessing knowledge of an asset's intrinsic value through access to comprehensive market information, engage in high-volume transactions and orders to maximize their informational advantages. These value-relevant orders influence the actions of other market participants and consequently affect market prices. Given the critical role of information asymmetry and its effects on traders' order behavior, the study of orders—rather than mere transactions—has gained prominence. Analyzing traders' behavioral patterns through their order prices, volumes, and types provides a clearer understanding of the price effects resulting from market participants' decisions. Considering the price impact of orders and the significance of the secondary market for Islamic treasury bills as a pivotal tool in the central bank's monetary policy and government financing, this study aims to investigate the price effects of order flow on the price fluctuations of Islamic treasury bills in the market. MethodsIn this article, according to the price effect of orders in the market, the order flow imbalance variable that shows the changes in supply and demand volume in the first line of the order book has been used. Therefore, the vector autoregressive model has been used to investigate the effect of order flow imbalance on treasury bill price changes. Therefore, to check the price effect of orders, 17 symbols of treasury bills in the over-the-counter market from 2021 to September 2023, which had the most trading days compared to other treasury bills, were used. Therefore, in this research by using the vector autoregressive model and analyzing it through the impulse response function, the effect of order flow imbalance on price changes is investigated in three categories of treasury bills with different maturities to investigate the impact of information asymmetry on orders. ResultsAccording to the findings obtained in this research, the order flow imbalance variable in long-term maturity treasury bills had a greater effect on price changes. Moreover, based on the analyses conducted using the impulse response function, in the event of a shock, the effect of order flow imbalance in long-term maturity treasury bills will remain for extended periods and affect price changes. However, the magnitude of the shock's effect on price changes is much greater than that of the order flow imbalance variable. ConclusionTherefore, it can be concluded that in long-term maturity treasury bills, the effect of information asymmetry in the order flow is greater than the other bills and can lead to price volatility. Hence, traders should pay more attention to the supply and demand volume of orders and other factors to prevent potential losses.